2012
DOI: 10.1007/s11103-012-9873-6
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis light-dependent protochlorophyllide oxidoreductase A (PORA) is essential for normal plant growth and development

Abstract: During skotomorphogenesis in angiosperms, NADPH:protochlorophyllide oxidoreductase (POR) forms an aggregate of photolabile NADPH-POR-protochlorophyllide (Pchlide) ternary complexes localized to the prolamellar bodies within etioplasts. During photomorphogenesis, POR catalyzes the light-dependent reduction of Pchlide a to chlorophyllide (Chlide) a, which is subsequently converted to chlorophyll (Chl). In Arabidopsis there are three structurally related POR genes, denoted PORA, PORB and PORC. The PORA and PORB p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 36 publications
4
46
0
Order By: Relevance
“…In angiosperms, during skotomorphogenesis in the dark, PORs combine with NADPH and Pchlide to produce a ternary complex that makes up the main protein component of the prolamellar body (PLB) in the etioplast (Schoefs and Franck 2003; Paddock et al 2012). The PLB, which has a lattice-like structure, also contains Chl precursors, carotenoids, and lipids (Rosinski and Rosen 1972; Selstam and Sandelius 1984).…”
Section: Introductionmentioning
confidence: 99%
“…In angiosperms, during skotomorphogenesis in the dark, PORs combine with NADPH and Pchlide to produce a ternary complex that makes up the main protein component of the prolamellar body (PLB) in the etioplast (Schoefs and Franck 2003; Paddock et al 2012). The PLB, which has a lattice-like structure, also contains Chl precursors, carotenoids, and lipids (Rosinski and Rosen 1972; Selstam and Sandelius 1984).…”
Section: Introductionmentioning
confidence: 99%
“…And, an increasing number of por mutants have been characterized in Arabidopsis to elucidate the roles of the three AtPOR isoforms in detail. For example, the porA mutant displays stunted chlorina phenotype and photoautotrophic growth defect, and hence provides direct evidence to support an essential role for AtPORA in normal plant growth and development (Paddock et al 2012); the porB and porC mutants do not exhibit any phenotypic changes at the whole plant or chloroplast ultrastructural levels. Nevertheless, the porB porC double mutant displays a severe xantha (highly chlorophyll-deficient) phenotype and is characterized by smaller prolamellar bodies in etioplasts and decreased thylakoid stacking in chloroplasts, thus providing good evidence for the redundant roles for AtPORB and AtPORC in maintaining light-dependent Chl biosynthesis in green plants (Frick et al 2003;Masuda and Takamiya 2004).…”
Section: Introductionmentioning
confidence: 86%
“…It is well known that the insertion or deletion in POR gene results in chlorine (Paddock et al 2012), severe xanthan (Frick et al 2003), or yellow/white variegation leaf phenotype in por mutants (Sakuraba et al 2013); and more severely, the simultaneous silencing of all the POR genes leads to an albino phenotype in POR-RNAi tobacco plants (Talaat 2013). Since the PjPORB identified in this study was found to have an intact gene structure and play a full function in Pchlide photoreduction, it is tempting to study whether there is link between PjPORB expression and the unique leaf color variation in P. japonica cv.…”
Section: Pjporb-overexpression Had Substantial Effect On Transgenic Pmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the PORA gene was selected to be confirmed by qRT-PCR. This gene is important for skotomorphogenesis and normal photomorphogenic development (Paddock et al, 2012). Differently from LHCB2.2 and PSBW, the expression of PORA increased from week 12 onwards (Fig.…”
Section: Gene Expression Analysis In Leaf Tissue -From the Dark To Thmentioning
confidence: 97%